Management and organisational behaviour : contemporary challenges and future directions - Wiesner, Retha; Millett, Bruce (Milton, Qld : J. Wiley, 2000)
Organisational behaviour and the contemporary environment. Managing individuals in organisations. Managing groups in organisations. Managing organisations. Managing the processes of organisational behaviour. Managing organisational dynamics.
Keywords: Management; Organization; Organizational behavior; Management